A history of British motorways - Charlesworth, George (Thomas Telford, 1984)
This account of the way political and social attitudes concerning motorways have evolved describes the early road policies before and between the two World Wars and goes on to cover the building accelerated in the 1960s; however, in the 1970s environmental and social attitudes plus the oil crisis started the ongoing downturn.